(untitled) (Economics and region, 2024)
The article examines the theoretical and methodological aspects of the synergy of investment, innovation and financial mechanisms in the development of resource provision of the tourism sector of Ukraine in wartime and in the post-war recovery period. The aim of the study is to provide a comprehensive theoretical and methodological substantiation and systematisation of these mechanisms for the effective restoration of tourism infrastructure and increase of the industry’s competitiveness. The article applies the methods of analysis and synthesis to identify the key factors and instruments that influence the integration of investment and innovation into financial support mechanisms. The results underline the importance of an integrated approach that includes coordination of investment revenues, introduction of new technologies and effective management of financial resources to improve the state of the tourism sector. The practical value of the article lies in the provision of specific recommendations for public authorities, local administrations and private investors, which can help in the development and implementation of strategies for the restoration and development of tourist facilities, ensuring their competitiveness at the national level.